2023
DOI: 10.30650/jik.v11i1.3700
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and nurse performance

Maridi Marsan Dirdjo,
Subhan R. Syahab,
Enok Sureskiarti
et al.

Abstract: Employee performance has always been a major challenge in the management of organizations such as hospitals. Measuring the performance of hospital employees, especially nurses, is a very interesting topic considering that nurses are the largest workforce, which is around 50-60% of all health workers in the hospital. Research on job satisfaction in nurses related to performance is still important to do, to encourage overall hospital performance. Purpose: aim this research is to examine the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…While these personnel were already content with their impact on impoverished communities, the positive effects of digitization further elevated their job satisfaction-a sentiment consistent with findings from various studies. Research conducted among bank employees (Ichbal & Ubaidillah, 2023), workers in the beauty service industry (Kim et al, 2023), and nurses (Dirdjo et al, 2023) consistently revealed a strong positive relationship between job satisfaction and job performance. In parallel, the microfinancing personnel's increased job satisfaction aligns with these established patterns, highlighting the profound impact of digitization on both efficiency and employee contentment.…”
Section: Microfinance Employee Experience On Digitized Operational Pr...mentioning
confidence: 97%
“…While these personnel were already content with their impact on impoverished communities, the positive effects of digitization further elevated their job satisfaction-a sentiment consistent with findings from various studies. Research conducted among bank employees (Ichbal & Ubaidillah, 2023), workers in the beauty service industry (Kim et al, 2023), and nurses (Dirdjo et al, 2023) consistently revealed a strong positive relationship between job satisfaction and job performance. In parallel, the microfinancing personnel's increased job satisfaction aligns with these established patterns, highlighting the profound impact of digitization on both efficiency and employee contentment.…”
Section: Microfinance Employee Experience On Digitized Operational Pr...mentioning
confidence: 97%
“…Furthermore, the impact of job satisfaction on job performance is a recurring theme in research across different sectors. Findings from studies on bank employees (Ichbal & Ubaidillah, 2023), employees in the beauty service industry (Kim et al, 2023), nurse performance (Dirdjo et al, 2023), and the performance of tax officials (Mac et al, 2023) all reveal a direct positive effect of job satisfaction on employee job performance. Additional studies by Nabilla et al (2023), Farsole (2023), Kurniawan (2023), andYusnita (2023) further affirm that job satisfaction plays a crucial role in positively influencing job performance.…”
Section: Workloads and Work Situationsmentioning
confidence: 99%